Nutrient injection: an efficient technique to increase plantain (Musa AAB) crop yield - Silva-Arero, Elías Alexander; Cardona, William Andrés; Bolaños-Benavides, Martha Marina; Morales-Osorno, Humberto (Agronomía Mesoamericana, 2022)
Introduction. There are alternative fertilization methods such as fertilizer injection to the pseudostem that present greater efficiency than traditional edaphic fertilization. Objective. To evaluate the effect of soil fertilization and nutrient injection on morphological variables and bunch weight of the plantain in soils of variable fertility. Materials and methods. Two experiments were established in the municipalities of Viota and Chaguaní, Cundinamarca, Colombia, in 2018. A completely randomized design in bifactorial arrangement was used. The two experiments were: Experiment A: two locations and two types of fertilization (traditional and soil chemistry) and Experiment B: two locations and four nutritive solutions (one based on amino acids and another one with nutrients, both in two proportions) and a control. The response variables were: bunch weight, days from flowering to harvest, diameter, and external length of the central finger. Results. Organic edaphic fertilization in Chaguaní soil had no effect on bunch weight compared to chemical sources. In Viotá, soil chemistry fertilization increased bunch weight compared to the use of traditional soil fertilization. This differential response is explained by the fact that in Chaguaní the soil had a higher exchange capacity, nutrient content, and organic carbon. The plants planted in Chaguaní produced heavier bunches (21.6 kg) compared to Viotá (19.0 kg), but in the last one the fingers of the bunch were shorter. The nutrient injection in both locations increased the plantain crop yield compared to the control without injection. Conclusions. A low dose of fertilizer in the high fertility soil had a similar effect on plantain production recorded in the low fertility soil that received a high dose of fertilizer. The injection of nutritive solutions should be validated as a complementary alternative to the traditional soil fertilization.